Navigation buoys as stepping-stones for invasive species - Rafael Metri; Cassiana Baptista-Metri; Yara Aparecida Garcia Tavares; Mariana Baptista Lacerda; Elliezer Lima Correia; Gésica da Costa Bernardo Soares; Pablo Damian Borges Guilherme (Ocean and Coastal Research)
The movement of ships between continents is one of the leading causes of the increased bioinvasion of benthic organisms, surpassing the geographical barriers that prevent the natural dispersal of species. Artificial floating structures, such as buoys, can also serve as secondary dispersers in the introduction of exotic species on a regional scale. This study describes the fauna associated with buoys demarcating the access channel to Paraná‘s ports, focusing on recording introduced invasive species. Biota samples were collected from 23 buoys from different estuary sectors and some on their fastening chains, resulting in 73 samples. A total of 88 taxa were identified, of which half were sessile organisms and half, vagile. All observed taxa were previously recorded in the region, but introduced species clearly predominate among the sessile organisms colonizing the buoys, representing over half of the taxa determined at the species level. Buoys showed differentiated communities depending on their estuary location, with introduced species accounting for a larger share of the fauna on buoys in more saline sectors, reflecting their adaptations to oceanographic factors such as marine influence and tidal-driven water exchanges or an ecophysiological barrier caused by lower salinities in the inner estuary. Considering the negative effects of non-native species in natural environments and economic activity, the facilitating action of artificial floating substrates like signaling buoys highlights the need for environmental monitoring programs and more frequent maintenance of these structures to help control bioinvasions.